Clinical and Electrographic Correlates of Bilateral Independent Periodic Discharges. Issue 3 (May 2018) - Freund, Brin; Gugger, James J.; Reynolds, Alexandra; Tatum, William O.; Claassen, Jan; Kaplan, Peter W.
Abstract : Purpose: Periodic discharges (PDs) are EEG patterns denoting brain dysfunction and ictal tendency. Their exact meaning regarding etiology and outcomes is not well known. In particular, bilateral independent PDs (BIPDs) are poorly described. Methods: We performed a retrospective, multicenter study evaluating neuroimaging, epileptic, clinical, and EEG correlates of BIPDs. Results: Twenty-five patients studied with a mean Glasgow Coma Scale 6.5 and modified Rankin scale 3.9 who underwent EEG monitoring, mean duration 287 hours (range 0.75–3, 216). Most common causes of BIPDs were cardiac arrest, Central Nervous System infections, and acute/chronic ischemic/hemorrhagic stroke. Most had subcortical and cortical injuries on neuroimaging. Most of the PDs ranged from 0.5 to 2 Hz in frequency, were of multiple phase types, and localized to the frontal head regions. Eighteen of 25 patients had clinical or electrographic seizures. There was a trend toward seizures in those with BIPDs with a history of epilepsy ( P = 0.08) and acute metabolic dysfunction ( P = 0.08), particularly with coincident acute structural lesions ( P = 0.05). Seizures were predicted by bilaterally symmetric frequencies ( P = 0.02) and trended toward higher likelihood with PD frequency <2 Hz ( P = 0.08). Two of 25 patients survived past discharge with modified Rankin scale <3. Cardiac arrest was associated with withdrawal of life-sustaining therapy ( P < 0.001). Conclusions: BIPDs arise from acute and chronic neurologic injuries, often associated with metabolic dysfunction. Outcomes are poor in this population. Seizures are common, particularly in patients with PDs that are of a lower frequency or are symmetric in frequency. Further study is warranted to evaluate the association between BIPDs and seizures, as well as functional and longer term outcomes.